Health risk assessment following exposure of operators to backpack-sprayed prothioconazole and its major metabolite in wheat fields in China - Li, Shuang; Mei, Chenghan; Wu, Xuemin; Li, Xuefeng; Pang, Sen (Frontiers in Environmental Science, 2023)
Introduction: Prothioconazole is a triazolinthione fungicide widely used to control diseases on various crops caused by Ascomycetes, Basidiomycetes, and Imperfecti fungi. However, in view of the rapid transformation of parent prothioconazole to its major metabolite prothioconazole-desthio during application and the fact that the latter is of higher toxicity, prothioconazole poses a potential threat to the health of operators in direct contact with it. Currently, very few studies have been carried out regarding prothioconazole and prothioconazole-desthio exposure. Methods: Therefore, a typical exposure scenario from wheat-planting provinces in China was chosen, and a motorized backpack-type sprayer was used as the application equipment. The actual exposure doses of prothioconazole and prothioconazole-desthio for mixers/loaders and applicators under different exposure routes were determined, and a tiered risk assessment was conducted considering different conditions. Results: The results of this study indicated that the exposure risk to operators after spraying with 30% prothioconazole oil dispersion was unacceptable in the primary risk assessment, while the risk was acceptable with integrated risk quotients less than 1 at a better level of protection. Moreover, the upper legs and hands were regarded as the most contaminated sections during the mixing/loading process, and legs were the most contaminated sections during spraying. Good protection equipment, such as hats, long-sleeve shirts, long pants, socks, shoes, and rubber or nitrile gloves, was effective at alleviating prothioconazole and prothioconazole-desthio exposure. This study aims to provide important references for the safe use and risk management of prothioconazole.